L’oeuvre au noir - Nadeau, Lisanne (Ciel variable)

(untitled) (Les Productions Ciel variable, 2006)
Abstract All of Paul Lacroix's works are imbued with his fascination with the marking of a vast, luminous surface of paper. From drawing to photogram, he attracts us with an unvarying, extremely coherent, inscription. His current production, however, is marked by an unprecedented passage into shadow. The very dark works open immense chasms. The constant reference to previous works - retouched, revisited - and the fleeting impression of light within the latest photograms offer the passage of time as the ultimate entrenchment. Intimacy and contemplation thus succeed the preceding bursts of light. To the gaze that had been, up to now, loving and sensual, Lacroix adds a more hidden tone, a certain depth of time.